Effect of Vitamin B6 in Deceasing of Pre-Menstrual Syndrome Incidence Among the Christian Junior High School Girls 1 Magelang - Anityo Anityo; Parmono Giri Kriswoyo; Saseno Saseno (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2014)
Menstruation is a normal monthly cycles in women infertile, however, it can causesuffering if it is accompanied by severe symptoms periodically before menstruation. Some cases suffer pre-menstrual syndrome. The purpose of this study was to determine the effect of vitamin B6 to decrease the incidence of premenstrual syndrome in junior high school student Christian 1 Magelang. The benefit of research was to obtain more knowledge about reproductive health. Students in the treatment group were given Vitamin B6, while those in the control group were given placebo capsules. The results show differences in decreasing rate of pre-menstrual syndrome between the treatment group and the control group. Statistical analysis of the paired samples t- test revealed significantly difference (p: 0.000). Junior high School students should be advised to consume vitamin B6. Health workers were recommended to conduct reproductive health education activities, especially in the handling of pre-menstrual syndrome. Continuation of research related to the effect of vitamin B6 in decreasing the incidence of pre-menstrual syndrome should be conducted.